A SHORT NOTE ON BANDS OF GROUPS - Davvaz, Bijan (IndoMS, 2015)
In this paper we give necessary and sufficientÂ conditions on a semigroup S that it be semilattice of groups, a normal bandÂ of groups, and a matrix of groups.DOI :Â http://dx.doi.org/10.22342/jims.21.1.151.19-23